PEDESTRIAN BEHAVIOR FOR DEVELOPING STRATEGY IN TOURISM AREA; AGENT-BASED SIMULATION - Nova Asriana (DIMENSI (Journal of Architecture and Built Environment), 2021)
Agent-based modelling is an approach to develop a design strategy in socio-related studies to understand pedestrian behavior by using simulation through validation using field observation. This study area has a historic city so that having several potential advantages as destination tourists and also having urban issues. Some facilities disseminate prosperous for domestic tourist destinations, transportation hubs (land and water-based transport), and public facilities. The purpose is to develop a design strategy of pedestrian behavior in urban space to be procedure based on computational modelling. By merging the result, it helps designers to depict pedestrian movement flow, permeability, and connectivity patterns, which represent the presumptions of the origins or source of movement, destinations, generators, and attractors of movement. This simulation examines and valuates spatial behavior models allowing to route preferences of each pedestrian in order to be used in the strategy of design process for architect, urban planner, or other designer stakeholders. The result will imply a walkable pedestrian-way design, where this approach of a pedestrian experience might be an effective tool in city planning.